Лабиринт смерти: [сборник] / Андрей Бадин ; художник А. Яцкевич - Бадин Андрей Алексеевич (АВЛАД, 1993)
Экземпляры: ф.5 (2004) / Инвентарный номер: 48234 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 15 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44